2021
DOI: 10.1172/jci.insight.142376
|View full text |Cite
|
Sign up to set email alerts
|

A STAT3 inhibitor ameliorates CNS autoimmunity by restoring Teff:Treg Balance

Abstract: Reestablishing an appropriate balance between T effector cells (Teff) and Tregs is essential for correcting autoimmunity. Multiple sclerosis (MS) is an immune-mediated chronic CNS disease characterized by neuroinflammation, demyelination, and neuronal degeneration, in which the Teff:Treg balance is skewed toward pathogenic Teffs Th1 and Th17 cells. STAT3 is a key regulator of Teff:Treg balance. Using the structure-based design, we have developed a potentially novel small-molecule prodrug LLL12b that specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 75 publications
2
14
0
Order By: Relevance
“…Moreover, NR4A1 has been identified as a potential therapeutic target in central nervous system autoimmune-based inflammation ( Rothe et al., 2017 ). ET1DIE transcription factor nodes included STAT3, a well-characterized driver of numerous autoimmune conditions ( Aqel et al., 2021 ) and as previously noted, was also identified as a ET1DRE node. They also included RELA, a subunit of the well-known pro-inflammatory mediator NFκB, which has known roles as a driver of autoimmune disorders ( Sun et al., 2013 ).…”
Section: Resultssupporting
confidence: 63%
“…Moreover, NR4A1 has been identified as a potential therapeutic target in central nervous system autoimmune-based inflammation ( Rothe et al., 2017 ). ET1DIE transcription factor nodes included STAT3, a well-characterized driver of numerous autoimmune conditions ( Aqel et al., 2021 ) and as previously noted, was also identified as a ET1DRE node. They also included RELA, a subunit of the well-known pro-inflammatory mediator NFκB, which has known roles as a driver of autoimmune disorders ( Sun et al., 2013 ).…”
Section: Resultssupporting
confidence: 63%
“…LLL12B has one of the smallest molecular weights (374 dalton) compared to other STAT3 inhibitors. In addition, our in vivo pharmacokinetic studies in rats indicated that LLL12B is orally bioavailable (38.0%) and stable in the plasma, producing drug levels 5-fold better compared to LLL12 [20]. These results support that LLL12B is a superior drug relative to LLL12 to target STAT3 in ovarian cancer cells.…”
Section: Plos Onesupporting
confidence: 61%
“…The small molecule LLL12B, a novel STAT3 inhibitor, was synthesized at University of Florida College of Pharmacy (Chenglong Li) [20]. LLL12B powder was dissolved in sterile dimethyl sulfoxide (DMSO) to make a 20 mM stock solution and stored at -20˚C.…”
Section: Methodsmentioning
confidence: 99%
“…We identified that LLL12B, a prodrug of LLL12, is activated by the tumor-associated plasmin through the hydrolytic cleavage of the carbamate ester bond to release LLL12 [ 26 ]. It directly binds to the pTyr705 binding site of STAT3 with improved in vivo pharmacokinetic properties relative to the parent drug LLL12, which supports that it has superior and selective inhibition of STAT3 [ 25 , 27 , 28 ]. In this study, we tested LLL12B in TNBC cells and the results showed that targeting STAT3 with LLL12B induced apoptosis and suppressed colony formation, migration, and tumor growth in TNBC cells.…”
Section: Introductionmentioning
confidence: 93%